Learners’ Study Habits and Academic Performance in Mathematics: A case study of Selected Public Secondary Schools in Ogun State, Nigeria - Asikhia Olubusayo Aduke, (African Journal of Education,Science and Technology (AJEST), 2025)
Mathematics is a major requirement for entrance into higher institutions, yet learners fail the subject and are unable to further their education. This study therefore examined the influence of learners’ study habits on the mathematics performance of public secondary school students in Ogun State, Nigeria. Three research hypotheses were used to generate data from 205 Senior Secondary School Students II (SS2) drawn through stratified random sampling.Secondary School Academic Performance Inventory (SSAP) and Study Habit Inventory (SHI were the two instruments used to collect information from respondents. A descriptive survey design was used to seek descriptive information from the learners. The data analysis method used was Pearson Correlation Co-efficient. Findings revealed that low, medium and high study habits levels of students have significant influence on their academic performance and that although there is a direct relationship between learners who have low and high study habits and their academic performances in mathematics, a negative relationship existed between students with medium study habit and their academic performances. Based on these findings, it was recommended among others that the Nigerian Educational Research and Development Council (NERDC) should include study habit techniques in the secondary school curriculum so that students particularly with low study habit can be well equipped with knowledge of study habit techniques; Measurement and assessment of students’ level of study habits for early detection and quick intervention should also be done as soon as students gain admission into the secondary school. Counsellors should also alert sensitise students on how to enhance effective study habits which could improve their academic performance in mathematics. Implications for teachers, counselors, policymaker, and curriculum planners emphasize the need to recognise the importance of emotional development of students and not only their cognitive development.